Local knowledge, use, and conservation of wild birds in the semi-arid region of Paraíba state, northeastern Brazil - Vanessa Moura dos Santos Soares (Journal of Ethnobiology and Ethnomedicine, 2018)
Abstract Background The use of wild birds, for several purposes, is directly associated with cultural, ecological, and conservation issues. This study aimed to inventory the wild birds known and used in three communities in Paraíba state, northeast Brazil, and to investigate the sociocultural context in which these activities occur. Methods A total of 179 people (98 women and 81 men) were interviewed. Data were collected through free interviews, using semi-structured forms, and posing questions about the use of local wild birds. The species were identified by direct observation of the birds, analysis of photographic records, and the use of a scientific guide. Results Each species’ use value (UV) was calculated in three different ways: UVgeneral, UVcurrent, and UVpotential. These UVs ranged from 0.01 to 1.15 for UVg, 0 to 0.21 for UVc, and 0.01 to 1.02 for UVp. A total of 99 species, 81 genera, and 40 families were recorded and classified into the use categories of food, breeding, and medicinal. Thraupidae (12 species), Columbidae, Accipitridae, and Icteridae (8 species each) were the most diverse families. Conclusions The use of wild birds is a widespread activity in the studied areas, where many species are used. This demonstrates the need to conduct studies to assess the pressure suffered by these bird species, as well as the need to create public policies that intervene in the use and conservation of wild birds.